Winter syndrome: about an uncommon case report - Slaoui, Aziz (BMC Womens Health, 2020)
BACKGROUND: Congenital genital tract outflow obstruction may occur at different levels and with different clinical presentations. Winter syndrome was first described in 1968 as an association of renal, genital and middle ear anomalies. This syndrome is characterized by autosomal recessive transmission, unilateral or bilateral renal hypoplasia, distal vaginal atresia, and moderate to severe conductive hearing loss with malformation of the ossicles. The diagnosis is usually made when symptoms of obstruction are obvious. It presents most commonly with primary amenorrhea in a girl with a normal XX genotype, ovarian and hormone function; and cyclical abdominal pain. Ultrasound confirm the physical examination, revealing the presence of a normal uterus and cervix, normal ovaries and fallopian tubes, and a large hematocolpos. CASE PRESENTATION: This case reports Winter syndrome in a 14-year-old girl which vaginal atresia was managed by a trans perineal vaginal pull through. CONCLUSIONS: Winter syndrome is a rare congenital condition whose clinical picture is that of an adolescent girl with primary amenorrhea and cyclic pelvic pain due to vaginal atresia, varying degrees of renal dysgenesis and deafness due to malformation of the ossicles of the middle ear. Diagnosis is based on clinical examination and imaging. Magnetic resonance imaging allows assessing the importance of atresia and thus guiding surgical management. The goals of surgical intervention are to provide relief from pain, ensure normal sexual intercourse and to preserve fertility. A thorough knowledge of embryology, pre-operative imaging with MRI and clinical examination is essential to plan an appropriate surgical management.